Activation of Serotonin 5-HT7 Receptors Modulates Hippocampal Synaptic Plasticity by Stimulation of Adenylate Cyclases and Rescues Learning and Behavior in a Mouse Model of Fragile X Syndrome - Costa, Lara; Sardone, Lara Maria; Bonaccorso, Carmela Maria; D’Antoni, Simona; Spatuzza, Michela; Gulisano, Walter; Tropea, Maria Rosaria; Puzzo, Daniela; Leopoldo, Marcello; Lacivita, Enza; Catania, Maria Vincenza; Ciranna, Lucia (Frontiers in Molecular Neuroscience, 2018)
We have previously demonstrated that activation of serotonin 5-HT7 receptors (5-HT7R) reverses metabotropic glutamate receptor-mediated long term depression (mGluR-LTD) in the hippocampus of wild-type (WT) and Fmr1 Knockout (KO) mice, a model of Fragile X Syndrome (FXS) in which mGluR-LTD is abnormally enhanced. Here, we have investigated intracellular mechanisms underlying the effect of 5-HT7R activation using patch clamp on hippocampal slices. Furthermore, we have tested whether in vivo administration of LP-211, a selective 5-HT7R agonist, can rescue learning and behavior in Fmr1 KO mice. In the presence of an adenylate cyclase blocker, mGluR-LTD was slightly enhanced in WT and therefore the difference between mGluR-LTD in WT and Fmr1 KO slices was no longer present. Conversely, activation of adenylate cyclase by either forskolin or Pituitary Adenylate Cyclase Activating Polypeptide (PACAP) completely reversed mGluR-LTD in WT and Fmr1 KO. 5-HT7R activation reversed mGluR-LTD in WT and corrected exaggerated mGluR-LTD in Fmr1 KO; this effect was abolished by blockade of either adenylate cyclase or protein kinase A (PKA). Exposure of hippocampal slices to LP-211 caused an increased phosphorylation of extracellular signal regulated kinase (ERK), an intracellular effector involved in mGluR-LTD, in WT mice. Conversely, this effect was barely detectable in Fmr1 KO mice, suggesting that 5-HT7R-mediated reversal of mGluR-LTD does not require ERK stimulation. Finally, an acute in vivo administration of LP-211 improved novel object recognition (NOR) performance in WT and Fmr1 KO mice and reduced stereotyped behavior in Fmr1 KO mice. Our results indicate that mGluR-LTD in WT and Fmr1 KO slices is bidirectionally modulated in conditions of either reduced or enhanced cAMP formation. Activation of 5-HT7 receptors reverses mGluR-LTD by activation of the cAMP/PKA intracellular pathway. Importantly, a systemic administration of a 5-HT7R agonist to Fmr1 KO mice corrected learning deficits and repetitive behavior. We suggest that selective 5-HT7R agonists might become novel pharmacological tools for FXS therapy.